2017
DOI: 10.25110/arqvet.v19i3.2016.6084
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação E Correlações De Parâmetros Microbiológicos Em Queijos Minas Frescal No Sudoeste Da Bahia

Abstract: Milton Rezende Teixeira Neto 1 MOTTIN, V. D.; SILVA, L. L.; ROCHA, J. N.; TEIXEIRA NETO, M. R. Quantificação e correlações de parâmetros microbiológicos em queijos minas frescal no sudoeste da Bahia. Arq. Ciênc. Vet. Zool. UNIPAR, Umuarama, v. 19, n. 3, p. 137-142, jul./set. 2016. RESUMO:O Queijo Minas Frescal é um dos derivados do leite mais consumidos no Brasil, considerado como um queijo semigordo e de muito alta umidade, característica que propicia a contaminação por micro-organismos. Nesse sentido, o obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…8 All cheese samples analyzed in this study showed high counts of S. aureus and the higher the count of S. aureus, the greater the possibility of having coagulase-positive species. Bacteria of the genus Staphylococcus have a habitat in humans and animals, being found on the skin, glands and mucous membranes, 9 and their presence in cheeses indicates that the raw material used may be from infected animals or that the product may have been handled under poor hygienic conditions, which may produce toxins when found in large quantities, and attention to hygienic issues in the handling of these products is important.…”
Section: Resultsmentioning
confidence: 99%
“…8 All cheese samples analyzed in this study showed high counts of S. aureus and the higher the count of S. aureus, the greater the possibility of having coagulase-positive species. Bacteria of the genus Staphylococcus have a habitat in humans and animals, being found on the skin, glands and mucous membranes, 9 and their presence in cheeses indicates that the raw material used may be from infected animals or that the product may have been handled under poor hygienic conditions, which may produce toxins when found in large quantities, and attention to hygienic issues in the handling of these products is important.…”
Section: Resultsmentioning
confidence: 99%
“…Os autores identificaram a presença de E. Coli em queijos coalhos e manteigas. A presença de E. Coli também foi relatado porMottin et al (2016) em queijos minas frescal,Soares et al (2018) em queijo artesanal, Morais e Silva Filho (2016)StaphylococcusStaphylococcus é um gênero bacteriano composto por cocos Gram-positivos anaeróbios facultativos, são geralmente patogênicos, em alguns casos podem causar colonização assintomática em indivíduos saudáveis(González-Martin et al, 2020). De acordo comJohler et al (2018) o Staphylococcus tem uma causa comum de intoxicações alimentares.…”
unclassified
“…A intoxicação alimentar ligada a Staphylococcus é atribuída com sua presença de pelo menos 5 células log por grama de alimento, capazes de produzir enterotoxinas estafilocócicas em alimentos(Hennekinne et al, 2010).A elevada contagem de Staphylococcus coagulase positiva em queijos indica eventuais falhas durante e após processamento do produto, tais como: pasteurização ineficiente, más condições de higienização dos equipamentos e dos manipuladores, utilização incorreta da temperatura de conservação e condições higiênico-sanitárias insatisfatórias, em geral falhas nas Boas Práticas de Fabricação. A maioria dos processadores de alimentos são portadores assintomáticos desses microrganismos nas mãos e nas fossas nasais, o que agrava os riscos de contaminação durante a manipulação(Mottin et al, 2016). SegundoSantos et al (2017), a contaminação de Staphylococcus coagulase positiva em produtos lácteos pode está relacionada com a sanidade do animal, são agentes patógenos da mastite, contaminando o leite.…”
unclassified